Tafsir Konstitusi Negara Dalam Keadaan Darurat (State Of Emergency) Dalam Menghadapi Darurat Kesehatan Masyarakat - Basri Effendi (Puslatbang KHAN, 2020)
Abstract, The Constitution has explicitly formulated on article 12 of the Year 1945 Constitution stating that: